Ensino médio organizado por blocos de disciplinas semestrais: avanços e limites no contexto escolar - Tomazi, Jeovania Fabro (2014)
Inserted into the search Society, Knowledge and Education of Masters in Education of UNIOESTE campus of Francisco Beltrão, Paraná, this research fits into the debate on education, labor and educational policies for secondary education. It has as object of study high school program organized in blocks of semester subjects in the state of Paraná and as objective to analyze the process of implementation, development and contradictions of this organization at school. Part of the hypothesis is that this proposal represented an emergency action ahead of government to lower results of high school without changing up the foundations of the educational system. The theoretical basis of this study follows the Marxist methodological option for believing that this provides elements that allow understanding the contradictions of those intended for high school education policies, as well as contributes to the display of new ways to understand the formation of young people in this stage of schooling. The starting point of this thesis is the understanding of the relationship education and work in a Marxist perspective of human omnilateral training. However, when analyzing the economic, political and cultural relations in capitalist society, resulting from changes in the production process, it is concluded that the reforms of the state and education go toward a unilateral human, based on neoliberal principles of flexibility and employability. The research follows analyzing the educational process of young people and the strategies developed by the state in encouraging the organization of focal proposals, in order to meet the needs of high school Brazilian. It discusses the approach of the organization of secondary education in blocks of semester subjects in the state of Paraná, with definitions of the policy outcome and the discourse of school autonomy. This dissertation concludes with an analysis of data concerning the qualitative research conducted in 2013 with students, teachers and educational staff from two schools of the state system who experienced reforms in secondary education in the state in recent years specifically related to High School program block semester subjects. Thus, it was possible to point out the contradictions with regard to the construction, deployment, and in the process of teaching and learning in this organization.